Advancing Islamic Religious Education Through ICT-Driven Pedagogical Innovation - Meriyati, Meriyati; Muzekki, Muzekki; Husnilawat, Husnilawat; Sari, Indah Nur Bella; Yansyah, M Eko Juli; Jatmiko, Agus; Amriyah, Chairul (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study conducts a systematic literature review drawing on 38 peer-reviewed articles to explore ICT-driven pedagogical innovation in Islamic Religious Education (IRE). The research addresses the following questions: How can ICT be effectively integrated to enhance IRE pedagogy while preserving Islamic ethical values? Using thematic analysis, 28 selected articles were analyzed to identify key themes including e-learning platforms, interactive media, teacher digital literacy, and digital content credibility. The findings highlight both opportunities for personalized, engaging learning and challenges such as infrastructural gaps and misinformation risks. The study contributes an original framework emphasizing the integration of Islamic digital ethics in ICT pedagogy. Limitations include the focus on English-language sources and the exclusion of empirical case studies. Future research should develop and test practical models of ethical ICT integration in diverse Islamic educational contexts.